A Tourism Conditions Index - Chia-Lin Chang; Hui-Kuang Hsu; Michael McAleer (Tinbergen Institute, 2014)
This paper uses monthly data from April 2005 to August 2013 for Taiwan to propose a novel tourism indicator, namely the Tourism Conditions Index (TCI). TCI accounts for the spillover weights based on the Granger causality test and estimates of the multivariate BEKK model for four TCI indicators to predict specific tourism and economic environmental indicators for Taiwan. The foundation of the TCI is the Financial Conditions Index (FCI), which is derived from the Monetary Conditions Index (MCI). The empirical findings show that TCI weighted by spillovers reveal greater significance in forecasting the Composite Index (CI), an economic environmental indicator, than the Tourism Industry Index (TII), which is an existing indicator for the tourism industry that is listed on the Taiwan Stock Exchange (TWSE). Moreover, previous values of the alternative TCI and TII are shown to contain useful information in predicting both tourism and economic environmental factors. Overall, the new Tourism Conditions Index is straightforward to use and also provides useful insights in predicting tourism arrivals and the current economic environment.
Keywords: B41; E44; E47; G32; 330; Monetary Conditions Index (MCI); Financial Conditions Index (FCI); Tourism Conditions Index (TCI); BEKK; Spillovers; Granger causality